Production of Σ baryons as a function of multiplicity in pp collisions at the LHC with ALICE - Gordeev Pavel (EPJ Web of Conferences)
In recent year, the production of charged Σ hyperons in pp and p–Pb collisions was measured by the ALICE collaboration using several techniques. Historically, the first one used the decay channel Σ+ → pπ0 with reconstruction of the proton with the tracking systems at mid-rapidity and the π0 in the electromagnetic calorimeter EMCAL or via the photon conversion method. The second technique used the decay channel ∑-± → n¯π± where charged pions are reconstructed with the tracking systems and the anti-neutron in the precise electromagnetic calorimeter PHOS. We present the transverse momentum spectra of charged Σ and its anti-particle measured in pp collisions at √s = 13 and √s = 5 TeV and compare them to predictions of several models. Finally, we discuss expectations from the Run 3 of LHC and in particular the possibility of Σ particle detection with the reconstruction of its decay after traversing several layers of the upgraded silicon tracker.